Forensic applications of high performance liquid chromatography - Bayne, Shirley; Carlin, Michelle (CRC Press/Taylor & Francis Group, 2010)
The book presents key point summaries and questions to enhance learning and test comprehension, provides a complete glossary of terms, and includes references at the end of each chapter to facilitate further study.